The complete mitochondrial genome of Channa maculata (Perciformes: Channidae). (August 2013) - Wang, Kaixi; Wang, Baosen; Li, Jiongtang; Chen, Kunci; Xu, Peng; Sun, Xiaowen
<x xml:space="preserve">Abstract</x> This paper reports the complete mitochondrial genome (mitogenome) sequence of Channa maculate (Taiwan snakehead). The mitogenome of Taiwan snakehead was determined to be 16, 558 bp in length. It contains 13 typical vertebrate protein-coding genes, 22 tRNA genes, 2 rRNA genes, 1 OL (putative light-strand origin of replication), and 1 putative control region (D-loop). This is the first report on the complete mitogenome sequence of Channa maculata.